2006
DOI: 10.1093/jac/dkl330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three standardized disc susceptibility testing methods for colistin

Abstract: Disc susceptibility testing methods are unreliable at detecting colistin resistance. Dilution methods should be the method of choice for susceptibility testing of colistin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 7 publications
6
69
0
4
Order By: Relevance
“…In the current study the disc diffusion although showing CA of 93% yet it failed to detect the two resistant A. baumanniii detected by the broth microdilution (reference method) giving VMEs, however, basing our findings on only these resistant strains is inconclusive but in the absence of verified guidelines, disc diffusion method should not be used alone in judging colistin susceptibility in A. baumanniii. Our finding is supported by others who reported disc diffusion to be an unreliable method for detecting polymyxins susceptibility [16] [27]. As regards Vitek 2 AST, we found it to be reliable and easy with 100% CA, Lee et al 2013 tested 213 isolates, including 13 colistin resistant Acinetobacter strains.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study the disc diffusion although showing CA of 93% yet it failed to detect the two resistant A. baumanniii detected by the broth microdilution (reference method) giving VMEs, however, basing our findings on only these resistant strains is inconclusive but in the absence of verified guidelines, disc diffusion method should not be used alone in judging colistin susceptibility in A. baumanniii. Our finding is supported by others who reported disc diffusion to be an unreliable method for detecting polymyxins susceptibility [16] [27]. As regards Vitek 2 AST, we found it to be reliable and easy with 100% CA, Lee et al 2013 tested 213 isolates, including 13 colistin resistant Acinetobacter strains.…”
Section: Discussionsupporting
confidence: 86%
“…Considerable variations exist regarding the species and selection criteria used, zone diameter breakpoints, and MIC susceptibility breakpoints. Several recent and older studies have found very major error rates of ϳ5% to 20% (isolates falsely identified as being susceptible) and have concluded that disk diffusion testing is unreliable (4,55,83,86,111,116,130,146,167,179). Therefore, despite the inclusion of disk diffusion testing guidelines by several groups, the accumulated data suggest that alternative methods should be used for susceptibility testing of polymyxins.…”
Section: Susceptibility Testing Methodologymentioning
confidence: 99%
“…The disc diffusion technique was reported to be an unreliable method for evaluating the susceptibility of bacteria to polymyxins because these antibiotics diffuse poorly in agar. Consequently results of polymyxin disk diffusion tests should be confirmed with a broth dilution method [14,15].…”
Section: Antimicrobial Resistancementioning
confidence: 99%